Предмет: Алгебра,
автор: stas455
Найти корень уравнения
(x-5)(x+8)-(x-7)(x+7)=3
Ответы
Автор ответа:
0
(x-5)(x+8)-(x-7)(x+7)=3
x^2+8x-5x-40-x^2+49=3
3x+9=3
3x=-9+3
3x=-6
x=-6/3
x=-2
Ответ: -2
x^2+8x-5x-40-x^2+49=3
3x+9=3
3x=-9+3
3x=-6
x=-6/3
x=-2
Ответ: -2
Автор ответа:
0
х+8 потому что от него зависит результат уравнения
Похожие вопросы
Предмет: Математика,
автор: knopkaaman
Предмет: Информатика,
автор: si0275018
Предмет: Физика,
автор: galakhovaag
Предмет: Химия,
автор: alekssandr16
Предмет: История,
автор: Аноним